Millennium Generation Work Experience - Liskuné Vathy , Veronika; Bognár , István Ádám; Kőmíves , Péter Miklós; Körösparti, Péter; Nagy , Adrián Szilárd (International Journal of Engineering and Management Sciences, 2020)
If we are open-minded in our everyday life, we should not overlook the phenomenon of student work. Within the framework of this study, our aim was to examine the work experience, later employment plans and income needs of students starting their studies at the Faculty of Economics at the University of Debrecen. In addition, we analyze the most important sources related to student work through literature studies.It is important to pay attention to changing attitudes of newcomers to higher education as they become active job seekers after graduation. At the Faculty of Economics of the University of Debrecen, about 1,700 students started their studies in the 2019/2020 academic year. Our research was conducted with the involvement of these students.The data were collected among students participating in the stork camp organized by the University of Debrecen. The survey covers, among other things, the initial salary requirements, previous work experience, future plans, including the willingness to work abroad, and factors that are taken into account when choosing a job.